Las metamorfosis de Eros. Poéticas del cuerpo enamorado en Rafael-José Díaz, Ada Salas y Eduardo Moga - Gijón, Mario Martín (Romanica Silesiana, 2021)
Until recent times, the representation of desire and erotics in Spanish poetry was quite scanty. Even now, there are few poets who explicitly deal with sex in their poetry. In this article, I analyse the work of three poets with different outlooks on desire: a homosexual male (Rafael-José Díaz), a heterosexual female poet (Ada Salas), and a heterosexual male poet (Eduardo Moga). Taking into account, among others, the theories of Roland Barthes (A Lover’s Discourse. Fragments) and Anne Carson (Eros the Bittersweet), I attempt to emphasise the originality of the language treatment of bodies in love.